From Sequence‐Defined Macromolecules to Macromolecular Pin Codes. Issue 8 (3rd March 2020) - Holloway, Joshua O.; Van Lijsebetten, Filip; Badi, Nezha; Houck, Hannes A.; Du Prez, Filip E.
Abstract: Dynamic sequence‐defined oligomers carrying a chemically written pin code are obtained through a strategy combining multicomponent reactions with the thermoreversible addition of 1, 2, 4‐triazoline‐3, 5‐diones (TADs) to indole substrates. The precision oligomers are specifically designed to be encrypted upon heating as a result of the random reshuffling of the TAD‐indole covalent bonds within the backbone, thereby resulting in the scrambling of the encoded information. The encrypted pin code can eventually be decrypted following a second heating step that enables the macromolecular pin code to be deciphered using 1D electrospray ionization‐mass spectrometry (ESI‐MS). The herein introduced concept of encryption/decryption represents a key advancement compared with current strategies that typically use uncontrolled degradation to erase and tandem mass spectrometry (MS/MS) to analyze, decipher, and read‐out chemically encrypted information. Additionally, the synthesized macromolecules are coated onto a high‐value polymer material, which demonstrates their potential application as coded product tags for anti‐counterfeiting purposes. Abstract : Macromolecular pin codes are obtained through the combination of the dynamic Alder‐ene reaction of 1, 2, 4‐triazoline‐3, 5‐dione (TAD) molecules with indole substrates and the Passerini three‐component reaction for the synthesis of tailor‐made, sequence‐defined macromolecules. The thermoreversible nature of the TAD‐indole reaction enables the encryption and decryption of the code and the read‐out is performed using electrospray ionization‐MS and liquid chromatography‐MS.